Traditional performances and creative art among the Shona people - Matiza, Vimbai M. (English Studies, Unisa, 2016)
The paper critically analyses Shona traditional performances and creative art among the Shona people. It proceeds from the argument that some scholars have argued that drama has its origins from traditional rituals. The discussion that the paper wants to advance is on the basis of giftedness where these ceremonies can be performed in a way that can be equated to drama in the European sense. In addition, the paper will have the liberty to examine some traditional performances which were done in the past and were qualified to be drama in that period. The argument of the paper is emanating from the idea that Zimbabwe has a history of theatre which emanates from its tradition. It is this history that can be traced back to numerous ceremonies, religious rituals and community festivals that define the existence of the people. It is against this notion that the paper seeks to argue the creativity of the Shona people through their traditional performances.